2001
DOI: 10.2527/2001.7971849x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high temperature and feeding level on energy utilization in piglets.

Abstract: The effect of temperature (23 or 33 degrees C) and feeding level on components of energy balance was studied in seven groups of individually reared Piétrain x (Landrace x Large White) littermate piglets. Within each litter, one pig was reared at 23 degrees C and given a predefined feeding level close to ad libitum (23AL pigs), one was reared at 33 degrees C and also fed close to ad libitum (33AL), and one was reared at 23 degrees C and pair-fed to the 33AL pig (23PF). Piglets of one litter were acclimated duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
5
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 0 publications
8
67
5
11
Order By: Relevance
“…These results suggest that the apparent efficiency of food utilization for growth would increase with time when temperature was above 288C. Brown-Brandl et al (2000) and Collin et al (2001a) showed a reduction of fasting heat production (FHP) under hot conditions in temperature-acclimated pigs. According to Koong et al (1982) and van Milgen et al (1998), this reduced FHP is generally explained by an indirect effect of reduced feed intake on viscera mass.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These results suggest that the apparent efficiency of food utilization for growth would increase with time when temperature was above 288C. Brown-Brandl et al (2000) and Collin et al (2001a) showed a reduction of fasting heat production (FHP) under hot conditions in temperature-acclimated pigs. According to Koong et al (1982) and van Milgen et al (1998), this reduced FHP is generally explained by an indirect effect of reduced feed intake on viscera mass.…”
Section: Discussionmentioning
confidence: 87%
“…According to these authors, this large variability can be explained by many factors including breed, BW, degree of fatness, diet composition and temperature range. The reduced ADFI under hot conditions in pigs leads to reduced thermogenesis and heat stress (Collin et al, 2001a). Most of the published results on the effect of elevated temperature on pigs performance were obtained in pigs previously acclimated to the experimental temperature for 3 to 10 days with a relative humidity ranging between 40% and 60%.…”
Section: Discussionmentioning
confidence: 99%
“…Esta hipótese está coerente com o relato de Santomá & Pontes (2004) de que o padrão de redução do consumo de ração aumenta de forma direta com a intensidade do estresse por calor, embora em uma relação não-linear. No entanto, de acordo com Collin et al (2001b), isoladamente, a redução do consumo diário de ração ocasionada pela alta temperatura não explicaria o menor ganho de peso pelos animais.…”
Section: Resultsunclassified
“…Neste trabalho, a deposição de gordura dos animais mantidos a 34ºC foi, em média, 25,6% menor (P<0,01) que a daqueles mantidos a 30ºC. Esses resultados corroboram os obtidos por Collin et al (2001b), que atribuíram a menor retenção de energia na forma de proteína e gordura nos animais, ao menor consumo de ração.…”
Section: Resultsunclassified
“…Furthermore, the SDM approach showed that habitats with greater suitability for feral pigs are those predominantly herbaceous (around 80% coverage), interspersed with patches of seasonally dry forest (optimum between 35 and 40% coverage) and not too far from water bodies (around one kilometer). S. scrofa has a low tolerance to high temperature in nature due to the lack of sweat glands or other efficient physiological cooling mechanisms (Baber & Coblentz 1986;Choquenot & Ruscoe 2003;Collin et al 2001;Huynh et al 2005b), and low ability to concentrate urine (Gabor et al 1997;Zervanos and Naveh 1988), being dependent on shaded habitats and reservoirs of water to avoid dehydration and promote thermoregulation (Baber & Coblentz 1986;Cuevas et al 2013b;Dexter 1998;Ilse & Hellgren 1995). Data available for southern Pantanal shows that the species has a high fidelity, returning to resting sites where they stay during the hottest hours of the day (OliveiraSantos 2013).…”
Section: Suitable Habitats and Limiting Factorsmentioning
confidence: 99%